ANALISIS AKTIVITAS ANTIOKSIDAN DAN KANDUNGAN ANTOSIANIN TOTAL EKSTRAK DAN LIPOSOM KELOPAK BUNGA ROSELLA (Hibiscus Sabdariffa L.) - I Gede Agus Juniarka; Endang Lukitaningsih; Sri Noegrohati (Faculty of Pharmacy, Universitas Gadjah Mada, 2011)
The form of liposome formulations is one of strategies to overcome the limitations of anthocyanin extract stability of roselle calyx (Hibiscus sabdariffa L.). In this study, antioxidant comparative analysis of antioxidant activity and total anthocyanin content from rosella extract and its liposomes form was conducted. Preparation of extract made by maceration using the best solvent consisted of methanol : formic acid (97:3) (v/v). From this procedure, the obtained extract was about 26.40% and antioxidant activity was 19.99%. Liposome formulations of methanol extract from roselle calyx were prepared by reverse phase method using rosella extract as aqueous phase and egg lecithin as the lipid phase. The stability of exctract and liposome form of rosella calyx was compared. The stability study showed that there was a reduction of antioxidant activity (DPPH test) 11.25 % for the roselle extract, while the liposome form was 0.93% after 30 days storage in low temperature (0-50C) and saturated nitrogen. In addition, total anthocyanin content (pH differential method test) decreased approximately 39.12 % for the roselle extract and 0.72% for the liposome form. More over, the liposome had lower level of irritation than the form of extract. Therefore, it can be concluded that anthocyanin encapsulated by liposome was more stable, safe, and effective than the anthocyanin of the rosella calyx extract.